Proceedings of the 4th International Conference on Foundations of Digital Games 2009
DOI: 10.1145/1536513.1536559
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of menu techniques using a 3D game input device

Abstract: Existing work on menu techniques has shown linear menus to be less efficient and reliable for menuing tasks when compared to radial menus. With the rise in popularity of 3D spatial interaction in console gaming, such as the Nintendo Wii, it is important to determine whether the existing findings still hold true when using a 3D pointing device such as the Wii Controller. Linear menus were compared with two other menu techniques: radial menus and rotary menus. Effectiveness was measured through task completion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Menu selection in 3D games was investigated in [4] using a Wii remote. Different menu types including linear, radial and rotary were compared.…”
Section: 4mentioning
confidence: 99%
“…Menu selection in 3D games was investigated in [4] using a Wii remote. Different menu types including linear, radial and rotary were compared.…”
Section: 4mentioning
confidence: 99%
“…World and body-referenced menus have the disadvantage of requiring the user to deviate his attention from the current task. To display the menu items, researchers have proposed a variety of 3 menu appearances, such as circular menus [59,28], radial menus [53,16], linear menus [16,19] or ring menus [23]. The appearance of the menu is usually linked to the input device or interaction technique used to interact with the menu.…”
Section: Menu Properties In Xr Environmentsmentioning
confidence: 99%
“…A similar result was obtained by Komerska and Ware [16] for their haptic menu system designed for Fishtank VR. Chertoff et al [7] designed a Nintendo Wiimote based menu system and found pie menus to be faster than linear lists. The results of all these studies are in line with Fitts's law [9], as pie layouts provide a smaller average distance to menu items.…”
Section: Related Workmentioning
confidence: 99%
“…Due to the availability of various unobtrusive motion sensing devices (e.g., Microsoft Kinect, Leap Motion, Creative Interactive Gesture Camera), many gesture based menu systems [4,7,10,24] have been explored both in academia and commercially in recent years. However, these menu selection methods are often slow (taking about 3-5 seconds) to perform and can suffer from accuracy problems making them less desirable compared to traditional keyboard-mouse or button based menu systems.…”
Section: Introductionmentioning
confidence: 99%